Can innovative methods of polymerization improve the physical-mechanical behavior of acrylic resins? - dos Santos, Daniela Micheline [UNESP]; Penitente, Paulo Augusto [UNESP]; da Silva, Emily Vivianne Freitas [UNESP]; Commar, Betina Chiarelo [UNESP]; Bento Laurindo Júnior, Murilo César [UNESP]; de Souza Batista, Victor Eduardo; Goiato, Marcelo Coelho [UNESP] (Elsevier, 2020)
Acrylic-based resin is the material of choice for the fabrication of definitive and provisional prostheses. In order to achieve clinical success, it is important to know the most suitable polymerization process for this material. The aim of this study was to evaluate the influence of different polymerization methods on several physical and mechanical properties, before and after thermocycling, of a heat-activated acrylic resin (HAAR). In addition, the degree of conversion (DC) was evaluated for all polymerization methods. Ninety HAAR samples were divided into three groups: conventional polymerization (CP), dry-heat polymerization (DHP), and digital pneumatic polymerization (DPP). Color, microhardness (n = 10), and flexural strength tests (n = 20) were performed, before and after 2000 cycles of thermocycling. The analysis of the DC was performed by using Fourier transform infrared spectroscopy (n = 4). Color alteration and DC data were submitted to one-way analysis of variance (ANOVA). Microhardness and flexural strength data were submitted to two-way repeated measures ANOVA. All results were submitted to the Tukey test (α = .05). The color alteration was statistically lower in the DHP group. The DPP group exhibited higher initial microhardness with a statistically significant difference from other the groups. There was no statistical difference between the groups in regards to flexural strength. The CP and DPP groups had higher DC results. The proposed polymerization methods had divergent results for the different properties analyzed. However, these results were similar to those of conventional polymerization, which is a viable and adequate alternative.
Keywords: Acrylic resins; Color; Flexural strength; Hardness; Interim dental prostheses; Polymerization; Polymethyl methacrylate